2021
DOI: 10.5194/acp-2021-933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two mega sand and dust storm events over northern China in March 2021: transport processes, historical ranking and meteorological drivers

Abstract: Abstract. Although a remarkable reduction in the frequency of sand and dust storms (SDSs) in the past several decades has been reported over northern China (NC), two unexpected mega SDSs occurred on March 15–20, 2021 and March 27–29, 2021 (abbreviated as the “3.15” and “3.27” SDS events), which has reawakened widespread concern. This study characterizes the origins, transport processes, magnitudes of impact, and meteorological causes of these two SDS events using a long-term (2000–2021) dust optical depth (DOD… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…However, this spatial heterogeneity was inconspicuous at 7:00 am. These disparities across space and time revealed that the dust transport process was strongly associated with the meteorological factor (mainly driven by north-westerly winds) and had a high magnitude, which is in accordance with the results of previous studies [40]. Moreover, on 29 March (average estimated PM 2.5 was 23.673 µg/m 3 ) (Figure 6c,d), a limited heterogeneity was observed, suggesting relatively homogeneous air quality patterns.…”
Section: Comparison With Other Methods Using the Photopm-daytime Datasetsupporting
confidence: 90%
“…However, this spatial heterogeneity was inconspicuous at 7:00 am. These disparities across space and time revealed that the dust transport process was strongly associated with the meteorological factor (mainly driven by north-westerly winds) and had a high magnitude, which is in accordance with the results of previous studies [40]. Moreover, on 29 March (average estimated PM 2.5 was 23.673 µg/m 3 ) (Figure 6c,d), a limited heterogeneity was observed, suggesting relatively homogeneous air quality patterns.…”
Section: Comparison With Other Methods Using the Photopm-daytime Datasetsupporting
confidence: 90%
“…Some hydroclimatic events with large impacts during recent decades in China can also be viewed as compound events, such as sand storms and saltwater intrusions. The severe sand storm in spring 2021 sweeping across northern China ( Gui et al., 2021 ) is a case in point. Sand storms are affected by both surface conditions (e.g., vegetation coverage and soil moisture) and meteorological factors (e.g., wind field and large-scale pressure fields) ( Xu et al., 2020 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…Lack of precipitation, excessive snowmelt, and strong evaporation resulted in dry soil. The loose and dry soil in Mongolia provided favorable conditions in dust sources [26,27]. The atmospheric river (Figure 2b) from the South China Sea to Northeast China may enhance the intensity of the Mongolian cyclone by providing more water vapor for latent heat release [39,40].…”
Section: Sand and Dust Storm Event Descriptionmentioning
confidence: 99%
“…Northern China experienced another SDS event on 27-29 March. This SDS event was much weaker than the SDS event on 14 to 15 March, with lower peak PM 10 concentrations [25,27]. In order to investigate the reliability of the gusty-wind model with the LS scheme, the same model configurations were used to simulate the SDS event on 27-29 March.…”
Section: The Role Of Gusty Windmentioning
confidence: 99%
See 1 more Smart Citation